PERTANGGUNG JAWABAN HUKUM TERHADAP PERJANJIAN ASURANSI KENDARAAN BERMOTOR AKIBAT HILANGNYA OBJEK PERTANGGUNGAN - Shamara Qanita; Sri Maharani Mardianingrum (Peneliti.net, 2023)
Insurance or insurance agreement is an agreement that provides protection against an event that occurs unplanned or cannot be known at the time of the agreement. In the agreement, there are legal subjects who bind themselves to each other in the insurance agreement, namely the insurer and the insured, each of whom has rights and obligations. All agreements that have been agreed upon by both parties are stated in a deed, namely a policy. The insurance policy must have provisions as stipulated in Article 1320 of the Indonesian Civil Code. The author adopts a normative legal methodology, doing research and drawing conclusions from existing works of literature, statutory and regulatory legislation, and insurance contract clauses. Written work by the author leads to the conclusion that, in the event of a covered loss, the insurer will pay the insured the full amount specified in the policy, regardless of who is at fault for the loss, but that the insurer will not pay out if the policy lacks provisions for classifying losses caused by the insured.